Comparaison entre la consommation maximale d'oxygène associée à la vitesse, déterminée par un test progressif et d'effort de 400m : implication pour la prescription d'entraînement de natation - Campos, E. Z. [UNESP]; Kalva-Filho, C. A.; Loures, J. P.; Manchado-Gobatto, F. B.; Zagatto, A. M. [UNESP]; Papoti, M. [UNESP] (Elsevier, 2017)
Objective Both 400 m peak oxygen consumption (VO2Peak) calculated using the backward extrapolation technique, and mean 400 m speed are used in swimming for training prescription. However, no comparison has been made between these variables observed after a 400 m effort and a free swimming incremental test, when both are performed unimpeded (without snorkel; enhancing its feasibility). Thus, we aimed to determine whether VO2Peak and its speed elicited after an incremental test may be interchangeable with these variables observed after a maximal 400 m effort. Methods Nine swimmers underwent a maximal 400 m effort, and an incremental test consisting of six 200m-stages. After the 400 m effort, and each stage of the incremental test, oxygen consumption was assessed through the backward extrapolation technique. The Student's t-test and Pearson correlation were adopted to analyze the results. Agreement analysis was also performed. Results No significant difference (P = 0.21) was observed between the VO2Peak after the 400 m effort (3.86 ± 0.85 L/min) and the incremental test (4.09 ± 0.93 L/min). A strong correlation was observed between then (r = 0.85; P < 0.05). The mean error was 0.23 L/min and the limit of agreement ±0.98 L/min. The speed associated with VO2Peak (1.39 ± 0.12 m/s) was higher (≈ 3.6%; P = 0.001) than the mean speed of the 400 m effort (1.34 ± 0.13 m/s), and they were highly associated (r = 0.96, P < 0.01). Conclusion VO2Peak and its relative speed might be used interchangeable with caution. The equation found in our study needs to be confirmed and improved on a larger population but it suggests the possibility for coaches to apply a correction to the mean speed of a 400 m swimming effort for training prescription.
Comparison between peak oxygen consumption and its associated speed determined through an incremental test and a 400-m effort: Implication for swimming training prescription
Keywords: Backward extrapolation; Incremental test; Peak oxygen consumption; Swimming